Light Metals 2014 2014
DOI: 10.1007/978-3-319-48144-9_229
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Mechanical and Electrical Properties of Aluminum-Based Composite Materials with Carbon Nanoparticles

Abstract: Nanocomposite materials with the matrix of an A356 alloy reinforced with 0.2 and 1 wt% of high-elastic nanodiamonds were produced by ultrasonic dispersion of nanoparticles in the melt followed by casting in a metallic mold. The structure as well as the physical and mechanical properties of the cast samples were examined using optical and scanning electron microscopy, hardness and tensile testing. It is shown that the hardness, Young's modulus and electrical resistivity increase with introduction of nanodiamond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It is known from various sources that ultrasound has a beneficial effect on deagglomeration of the nano-particle clusters [2][3][4][5][6]. This is explained by the phenomenon of acoustic cavitation, which includes the formation, growth, pulsation and collapse of gas bubbles.…”
Section: Modeling the Breaking Up Of Nano-particle Agglomeratesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known from various sources that ultrasound has a beneficial effect on deagglomeration of the nano-particle clusters [2][3][4][5][6]. This is explained by the phenomenon of acoustic cavitation, which includes the formation, growth, pulsation and collapse of gas bubbles.…”
Section: Modeling the Breaking Up Of Nano-particle Agglomeratesmentioning
confidence: 99%
“…Recent papers showed a clear increase in aluminum Young's modulus (by up to 100%) and in hardness (by up to 50%) with the addition of carbon nanoparticles [2]. Another study indicated a slight enhancement in Brinell hardness of aluminum, magnesium and copper based MMNCs with Al2O3 and AlN nanoparticles [3].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For aluminum melt, the dynamic viscosity l f = 0.0013 Pa s. Assuming the interfacial energy c sl = 0.2 to 2.0 J/m 2 , Eq. [1] yields v f =100 to 1000 m/s. Such fluid velocity values can be locally achieved instantaneously as a result of the collapse of cavitation bubbles induced by the ultrasonic field.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, applying electromagnetic induction stirring in combination with ultrasonic vibrations was found beneficial for nanoparticle dispersion in metal melts. [1,12] To improve the understanding of how this process works from the modeling point of view, the cavitation process is first examined. In the following section, a high-order acoustic model is presented, coupled with a model of cavitation.…”
Section: Introductionmentioning
confidence: 99%